In vivo Wnt signaling tracing through a transgenic biosensor fish reveals novel activity domains - Moro, E.; Ozhan-Kizil, G.; Mongera, A.; Beis, D.; Wierzbicki, C.; Young, R.; Bournele, D.; Domenichini, Alice; Valdivia, L.; Lum, L.; Chen, C.; Amatruda, J.; et al. (2012)
The creation of molecular tools able to unravel in vivo spatiotemporal activation of specific cell signaling events during cell migration, differentiation and morphogenesis is of great relevance to developmental cell biology. Here, we describe the generation, validation and applications of two transgenic reporter lines for Wnt/?-catenin signaling, named TCFsiam, and show that they are reliable and sensitive Wnt biosensors for in vivo studies. We demonstrate that these lines sensitively detect Wnt/?-catenin pathway activity in several cellular contexts, from sensory organs to cardiac valve patterning. We provide evidence that Wnt/?-catenin activity is involved in the formation and maintenance of the zebrafish CNS blood vessel network, on which sox10 neural crest-derived cells migrate and proliferate. We finally show that these transgenic lines allow for screening of Wnt signaling modifying compounds, tissue regeneration assessment as well as evaluation of potential Wnt/?-catenin genetic modulators. © 2012 Elsevier Inc.